2007
DOI: 10.1002/jcp.21049
|View full text |Cite
|
Sign up to set email alerts
|

MEK/ERK‐dependent uPAR expression is required for motility via phosphorylation of P70S6K in human hepatocarcinoma cells

Abstract: Motility and invasiveness events require specific intracellular signaling cascade activations. In cancer liver cells, one of these mechanisms could involve the MAPK MEK/ERK cascade activation which has been shown over expressed and activated in hepatocellular carcinoma. To study whether the MEK/ERK cascade is involved in the motility of HCC, we examined the effect of MEK inhibitor and ERK2 silencing using monolayer wound-healing assays and fluoroblock invasion systems. Evidence was provided that the MAPK casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
3
22
0
Order By: Relevance
“…16 In fact, the MAPK pathway is known to affect phosphorylation of Raptor, p70S6K and RSK, thereby inducing S6 phosphorylation. [47][48][49] Incidentally, we observed that inhibition of MEK did not inhibit the MTOR pathway in some cell lines. This may provide the opportunity to elucidate MTOR-independent effects of MEK inhibition.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…16 In fact, the MAPK pathway is known to affect phosphorylation of Raptor, p70S6K and RSK, thereby inducing S6 phosphorylation. [47][48][49] Incidentally, we observed that inhibition of MEK did not inhibit the MTOR pathway in some cell lines. This may provide the opportunity to elucidate MTOR-independent effects of MEK inhibition.…”
mentioning
confidence: 79%
“…Inhibitors of MEK can indirectly inhibit the MTOR pathway in a cell type-specific manner, because MEK/ERK phosphorylates and activates raptor, p70 S6K and RSK, thereby leading to phosphorylation of S6. [47][48][49] Importantly, inhibitors of MEK completely eliminated cyclin D1, regardless whether they suppressed MTOR or not (compare U0126 effects in HT-p21 versus MEL10 cells). In contrast to HT-p21 cells, U0126 treatment did not result in inhibition of MTOR in MEL10 cells, but inhibited cell proliferation, thus causing senescence in these cells, instead of suppressing it.…”
Section: Discussionmentioning
confidence: 99%
“…Other data strongly support the role of the MEK/MAPK pathway in the resistance of breast cancer cells to gefitinib and provide the rationale for novel therapeutic approaches based on combinations of signal transduction inhibitors (Normanno et al, 2006). Some recent studies have been conducted on MEK/ERK pathway by RNA interference (RNAi) in tumor cell lines suggesting a specific role of each isoform (ERK1/2) to contribute to a regulated cell cycle, motility and apoptosis progression (Vantaggiato et al, 2006;Bessard et al, 2007). Dominant-negative forms of ERK, and also ERK antisense nucleotides, inhibited proliferation of NIH 3T3 fibroblasts (Pages et al, 1993).…”
Section: Introductionmentioning
confidence: 85%
“…Several reports from the literature show that ERK1 and ERK2 have different functions (30). Although ERK1 is linked to cell proliferation and the survival of tumor cells (30), ERK2 has been linked to the regulation of cell motility (31). Thus, the activation of ERK1 in MCF-7 CisR cells can contribute to increased cell proliferation and cell survival.…”
Section: Discussionmentioning
confidence: 99%